Analisa Penyebab Getaran pada Sistem Rem Kendaraan Roda Empat Jenis Transmisi Otomatis - Dwiki Novandi; Didik Sugiyanto; Rolan Siregar (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2022)
A vehicle is said to be good if it can provide a sense of security and comfort for the driver. All types of two-wheeled, four-wheeled and heavy vehicles are equipped with a brake system that functions to reduce and stop the speed of the vehicle or allow the vehicle to park in a downhill area. The purpose of this study was to analyze the brake system disturbances in four-wheeled vehicles with automatic transmission types, especially the causes of vibration in the brake system. In analyzing the brake system disturbance, several tools are needed to support the data collection process, including caliper, micrometer, and dial gauge. The causes of brake system disturbances on Honda Mobilio cars and the handling that must be done when a disturbance occurs in the Honda Mobilio brake system. From the results of the measurement of the run out of the disc rotor, the difference in variations reaches 0.059 mm so that the disc rotor must be lathe. After turning the disc rotor, the result of the run out measurement is 0.003 mm and the thickness obtained is 20.702 mm which is still within the tolerance limit for use